2019
DOI: 10.2478/jtim-2019-0023
|View full text |Cite
|
Sign up to set email alerts
|

Effect of weight reduction on histological activity and fibrosis of lean nonalcoholic steatohepatitis patient

Abstract: Background and Objectives Weight reduction has evidenced benefit on attenuation of histological activity and fibrosis of nonalcoholic steatohepatitis (NASH), but there is scarcity of data for lean NASH subgroup. We have designed this study to compare the effects of weight reduction on histological activity and fibrosis of lean and non-lean NASH. Methods We have included 20 lean and 20 non-lean histologically proven NASH patients. BMI < 25 kg/m2 was defined as non-lean. Informed consent was taken from each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 35 publications
2
25
0
1
Order By: Relevance
“…Similar findings were observed in a study from Turkey where 5% body weight loss induced MAFLD remission in both obese and lean patients with MAFLD [288]. Similarly, a small biopsy-based study revealed that 5% weight reduction is associated with improvement of steatohepatitis in non-obese patients, similar to that which is observed in obese patients [289]. Larger biopsy-based studies are required to confirm the findings.…”
Section: Special Groupssupporting
confidence: 82%
“…Similar findings were observed in a study from Turkey where 5% body weight loss induced MAFLD remission in both obese and lean patients with MAFLD [288]. Similarly, a small biopsy-based study revealed that 5% weight reduction is associated with improvement of steatohepatitis in non-obese patients, similar to that which is observed in obese patients [289]. Larger biopsy-based studies are required to confirm the findings.…”
Section: Special Groupssupporting
confidence: 82%
“…13,30,31,40,45 Eight studies were of Caucasian origin 11,17,30,31,38,39,44,45 and 14 studies were of East-Asian origin. 11,12,16,17,28,29,[32][33][34][36][37][38][39][41][42][43][44] Two studies 4,6 presented values as median (range), five studies [14][15][16]19,21 presented as median (IQR), and rest of the studies [1][2][3]5,[7][8][9][10][11][12][13]17,18,20,22 presented...…”
Section: Resultsmentioning
confidence: 99%
“…For example: successful weight reduction strategy has potential benefits in nonlean patients but there are limited benefits in lean NAFLD patients. 21 Based on the previous literature and considering the differences in the underlying mechanisms of lean and nonlean NAFLD, we hypothesized that risks factors of NAFLD might differ between those groups and needs to be assessed. Therefore, the aim of this study was to systematically evaluate the risk factors of lean NAFLD and to aid in management strategies for the prevention and control of NAFLD and related diseases.…”
Section: Introductionmentioning
confidence: 99%
“…The concept that everyone has their own personal fat threshold [52] suggests that weight loss decreasing adiposity below the fat threshold might be beneficial metabolically and to the liver. In fact, in a small study with 20 lean-NAFLD patients, any weight loss was associated with steatosis improvement, and being above 5% corporal weight was associated with improvement in NAFLD activity score [168] .…”
Section: Managementmentioning
confidence: 96%